German and Polish Reviews of the Collection of Lithuanian Folksongs Dainos (1825) Edited by Rėza - Citavičiūtė, Liucija (Tautosakos darbai, 2017)
The first collection of Lithuanian folksongs Dainos, oder litthauische Volkslieder with translation into German, an introductory article and commentaries was edited and published in 1825 by the professor of Königsberg University Martynas Liudvikas Rėza (Martin Ludwig Rhesa, 1776–1840). In 1825–1827, this songbook received several reviews in German and Polish press. Among nine currently available reviews, only three – by Jakob Grimm, Johann Wolfgang von Goethe and an anonymous author – have seen publication in Lithuania (by Albinas Jovaišas in 1969 and Domas Kaunas in 1993). The author of this article has discovered in the German libraries as many as five reviews hitherto unknown in Lithuania, printed in prestigious journals of science and art, and three announcements, out of which one was here published by Goethe. These sources have been translated into Lithuanian and are published here for the first time. The author of the article focuses on the insights by the reviewers, describes publications in which these reviews were included, and identifies the anonymous authors.
Keywords: -